2004
DOI: 10.3141/1899-13
|View full text |Cite
|
Sign up to set email alerts
|

Observed Driver Glance Behavior at Roadside Advertising Signs

Abstract: Express routes in North America are becoming more crowded, both in traffic density and in visual clutter. Higher demand for driver attention is a possible concern for regulators. Advertising signs add to this demand on visual attention. This study focused on the glance behavior of 25 drivers at various advertising signs along an expressway in Toronto, Ontario, Canada. The average duration of the glances for the subjects was 0.57 s [standard deviation ( SD) = 0.41], and in total there was an average of 35.6 gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(32 citation statements)
references
References 9 publications
0
30
0
2
Order By: Relevance
“…Eight studies (Beijer et al 2004; Chan et al 2010; Divekar et al 2012; Dukic et al 2013; Kettwich et al 2008; Lee et al 2007; Perez et al 2012; Smiley et al 2004) reported data regarding long glances toward billboards. There was considerable evidence that 10–20% of glances made at billboards were ≥ 0.75 s in duration.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies (Beijer et al 2004; Chan et al 2010; Divekar et al 2012; Dukic et al 2013; Kettwich et al 2008; Lee et al 2007; Perez et al 2012; Smiley et al 2004) reported data regarding long glances toward billboards. There was considerable evidence that 10–20% of glances made at billboards were ≥ 0.75 s in duration.…”
Section: Resultsmentioning
confidence: 99%
“…The distracted driving problem is also likely to increase because of the emergence of digital billboards and other signage that introduce further visual clutter to the driving environment. (Beijer, Smiley, & Eizenman, 2004;Smiley, Smahel, & Eizenman, 2004;Wallace, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…[10] [11] The luminance contrast with the background of the ad space is the ratio of the luminance difference between the observed object and the luminance of the background. Large values of luminance contrast can blind drivers [12]. The possibility of misleading the driver is a dangerous aspect of road safety.…”
Section: Introductionmentioning
confidence: 99%